The Anti-Bogomil Anathemas in the Synodikon of Tsar Boril and in the Discourse of Kosmas the Presbyter against the Bogomils - Totomanova, Anna-Maria (Studia Ceranea, 2019)
During the last dеcade the history of the Synodikon of the Оrthodoxy in Medieval Bulgaria has been tackled upon from different points of view. The author of this paper provided substantial evidence proving that the Synodikon of Tsar Boril did not survive in its original form. By the end of the 14th c. the original translation was amended and edited in order to be installed in a canonical-liturgical compilation (archieratikon) that includes texts and services related to the Feast of Orthodoxy. The compilation is kept in the National Library in Palauzov’s collection No 289. Additional information about the different sources of some rubrics of the Synodikon, which do not correspond to its Greek version, was also provided. Recently we have discovered that the text, preserved in a collection of Damasckin type from the beginning of 16th c. (Drinov’s copy) represents indeed a compilation: its first part (the canonical one) contains the translation of the Palaeologan version of the Synodikon, which survived also in a triodion from the Library of the Romanian Academy of Sciences. The second part of the compilation however coincides with the text of the Synodikon of Tsar Boril with all amendments related to the Bulgarian history – rulers, patriarchs, bishops and nobles. This “Bulgarian” part of the Synodikon includes a series of anathemas against Bogomils, that do not have Greek correspondences and generally repeat the anti-Bogomils anathemas taken from the Letter of Patriarch Kosmas in a simpler language more understandable to the faithful. This paper is tracing the connection between these anathemas and the Anti-Bogomils anathemas in the Discourse of Kosmas the Presbyter against the Bogomils.